A strategy to implement a Software Defined Networking controller in a space launcher⁎. Issue 10 (2018) - Petit, Dorine; Georges, Jean-Philippe; Divoux, Thierry; Regnier, Bruno; Miramont, Philippe
Abstract: Nowadays, networks need to take care about several metrics. In the case of space launcher, the Quality of Service (QoS) items are availability, real time and observability. In addition, events like failure or stage separation need a modification of the configuration during the flight respecting QoS purposes. In order to unify these QoS items and apply an online reconfiguration, a SDN centralized architecture is chosen. This paper proposes a methodology to implement a SDN controller that computes the forwarding plane taking into account the end-to-end delays requirement. Then, the methodology is considered in the case study of a space launcher application with the French Space Agency (CNES).